Tertiary Education–Private Sector Engagement: A Strategic approach to catalysing innovation, economic revitalisation, and inclusive development in CARICOM countries - Rampersad, David, Howe,Glenford; Kassim, Halima-Sa’adia; (Revista Educación Superior y Sociedad (ESS), 2019)
This article provides an analytical framework for assessing and facilitating productive collaborations between the higher education sector and the private sector in the Caribbean. It argues that such partnerships can be crucial to economic growth, innovation and inclusive development in the region. The paper however points to certain challenges which must be tackled if meaningful and lasting benefits for the region are to be derived and maximised. These include addressing the lack of clarity in definition of the private sector as well as tackling the weak institutional capacities and the paucity of effective strategic partnerships among Caribbean higher education institutions.”..